Life Cycle Assessment a Coal Mining in East Kalimantan - Diharjo, Deniela Flora Mariyne Wongso; Manik, Yosef Barita Sar (Universitas Pendidikan Ganesha, 2023)
A Life Cycle Assessment study aimed at identifying the environmental impacts of a coal mining process has been carried out. The scope of the process includes land clearing to coal barging (cradle to gate). The functional unit used is the production of 1 ton of coal. The inventory data in this research is site specific, collected from a mining company located in East Kalimantan during the period September 2022 to June 2023. Impact analysis was characterized using the ReCiPe 2016 midpoint (H) method with the help of OpenLCA v.2.0.2 software. From the impact analysis, it was found that the coal mining operations studied have the potential to produce Fine Particulate Matter Formation (0.122 kg PM2.5eq), Global Warming (73.28 kg CO2eq), Terrestrial Acidification (0.4114 kg SO2eq), Ozone formation-human health and Ozone formation-terrestrial ecosystems (0.54 kg NOx eq), Land Use (4.42×10-4 m2a crop eq), and Water consumption (11.44 m3). The potential for Particulate Matter Formation and Global Warming is generally related to the process of moving materials and water consumption caused by the process of transporting coal. From this research, it was found that the overburden stripping process is an environmental hotspot for the coal mining process because it has the greatest potential impact of all existing processes.